Five-year changes in anterior segment parameters in an older population in urban southern China: the Liwan Eye Study. Issue 4 (4th September 2019) - Jiang, Yu; Wang, Decai; Wang, Wei; Chen, Feng; Wang, Lanhua; Scheetz, Jane; Huang, Wenyong; Huang, Shengsong; He, Mingguang
Abstract : Purpose: To investigate the 5-year changes in static and dynamic anterior segment optical coherence tomography (AS-OCT) parameters and their predictors. Methods: This was a prospective, population-based cohort study of people aged 50 years and older residing in the Liwan District, Guangzhou, China. Standardised AS-OCT scans were performed in November 2008 and November 2013 under dark and light conditions. Customised software was used to analyse horizontal AS-OCT images. Parameters in dark and measurements of light-to-dark changes were used for analyses. Results: A total of 186 (71.8%) subjects underwent AS-OCT twice, 5 years apart and were included for analyses. The mean age in 2008 was 64.7±7.0 years, and 60.2% were women. The anterior chamber width (ACW) decreased from 11.74±0.44 mm in 2008 to 11.60±0.37 mm in 2013 (p=0.001). There was a trend towards a decrease in dynamic capacity (light-to-dark changes) in the anterior segment, with decreased iris thickness at 750 µm (ΔIT750), ΔACW, Δ anterior chamber area (ACA) and Δ pupil diameter at 5 years (all p<0.05). After adjusting for age and sex, the following baseline parameters were associated with a greater decrease rate in trabecular iris space area at 500 µm (TISA500) at 5 years: TISA500, IT750 and ACA in dark (p<0.001 for all). Conclusions: Anterior chamber angle width decreased and the amount of light-to-dark changes declined during 5-year follow-up. Subjects with greater height, wider angle width and thicker iris at baseline have greater angle narrowing at follow-up.